The dysfunctional innate immune response triggered by Toll‐like receptor activation is restored by TLR7/TLR8 and TLR9 ligands in cutaneous lichen planus. (1st January 2015) - Domingues, R.; de Carvalho, G. Costa; da Silva Oliveira, L.M.; Futata Taniguchi, E.; Zimbres, J.M.; Aoki, V.; da Silva Duarte, A.J.; Sato, M.N.
Summary: Background: Lichen planus (LP) is a chronic inflammatory mucocutaneous disease. Toll‐like receptors (TLRs) bind numerous exogenous and endogenous antigens by recognizing conserved pathogen‐associated molecular patterns (PAMPs) and have the ability to induce the production of proinflammatory cytokines. Therefore, alterations in innate immunity could explain the inflammation and T‐cell autoreactivity leading to the development of LP disease. Objectives: To evaluate how the host innate immune response to PAMPs is affected by cutaneous LP, primarily by using TLR agonists to induce proinflammatory cytokine secretion from peripheral blood mononuclear cells (PBMCs). Methods: PBMCs from patients with LP and healthy control (HC) individuals were stimulated with agonists of TLR2/TLR1 (pam3csk4), TLR3 [poly(I:C)‐RIG], TLR4 (lipopolysaccharide), TLR5 (flagellin), TLR7 (imiquimod), TLR7/TLR8 (CL097) and TLR9 (CpG). Cytokines from culture supernatants ( n = 10–12) and serum chemokines and cytokines ( n = 22–24) were measured using flow cytometry. Results: Activation through the TLR2, TLR4 and TLR5 pathways induced increased tumour necrosis factor (TNF)‐α secretion by PBMCs from individuals with LP compared with the HC group. In contrast, activation through TLR3 and TLR7 was impaired in the LP group, leading to decreased TNF‐α secretion. Moreover, intracellular TLR activation resulted in reduced interleukin (IL)‐1β and IL‐6 secretion. Notably, individuals with LP became responders on stimulation with TLR7/TLR8 and TLR9 agonists; responses were measured as increases in interferon (IFN)‐α production. Detectable TNF‐α and high CXCL9 and CXCL10 serum levels were observed in patients with LP, suggesting their potential use as markers of the inflammatory status in LP. Conclusions: These findings point to a defect in the TLR signalling pathways in cutaneous LP. Agonists of TLR7/TLR8 or TLR9 overcame impaired IFN‐α secretion in LP, strategically acting as adjuvants to improve the type I response.